PENGARUH STRUKTUR KEPEMILIKAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2009-2012) - WIDYANJAYA, BOBBY RIYANDI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The importance of timeliness of financial reporting of a company has been recognized for a long time by the accountants, managers and financial analysts. Timeliness is one of the requirements for an information can be useful, when information is presented too late then the value contained irrelevant to the existing circumstances. The financial statements for the company which is a medium to convey information at a given time and the financial performance of the company should be beneficial to users, for it to be reporting must be timely. However, there is still a phenomenon that occurs a delay in the delivery of financial statements of public companies in Indonesia. Based on this phenomenon this research to expand understanding of the causes of the phenomenon. This study aims to analyze the effect of ownership structure on the timeliness of corporate financial reporting at public companies in Indonesia. The ownership structure is referred to in this study is the concentration of ownership, institutional ownership and foreign ownership. Using a sample of 289 companies with four time periods from 2009 to 2012, this study uses logistic regression in the analysis of statistical data. The first hypothesis is supported by the results of the data analysis, which proved that the phenomenon is true delays still occur in the financial reporting of public companies in Indonesia amounted to 27.1 percent. Two-a hypothesis supported, where institutional ownership significant negative effect on the financial reporting delay. While the concentration of ownership and foreign ownership is not supported his hypothesis in its influence on the financial reporting delay.